2008
DOI: 10.1159/000163021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Erosive, Cariogenic or Combined Erosive/Cariogenic Challenges on Human Enamel

Abstract: Individuals with cariogenic diet can also consume erosive beverages. Thus, it seems necessary to investigate a possible caries/erosion interaction. To test in situ/ex vivo a combination of these challenges, 11 subjects wore intraoral appliances containing four enamel blocks randomly assigned. In the first 2-week phase, the appliances were immersed in a cola drink 3 times/day. Two blocks were free of plaque (erosion only: EO) and two blocks were covered with plaque (erosion + plaque: EP). In the second 2-week p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
27

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 74 publications
3
28
0
27
Order By: Relevance
“…1,8,10,11,16,23,24 The in situ study design here using two erosive challenges per day (0.65% citric acid, pH 3.6) appears relatively slight but should reflect situations that can occur in patients with incipient erosion (2.7 μm -4.8 μm). [25][26][27] As expected, in the present study, the profilometric analysis showed that the lowest tissue loss was observed in the fluoride-treated group (AmF/NaF/SnCl 2 solution containing 500 ppm F -, 800 ppm Sn 2+ , pH = 4.5) compared to the control group. The tin-containing solution was effective in inhibiting enamel surface loss in other in vitro 4,5,[28][29][30] and in situ 16,31 studies.…”
Section: Discussionsupporting
confidence: 86%
“…1,8,10,11,16,23,24 The in situ study design here using two erosive challenges per day (0.65% citric acid, pH 3.6) appears relatively slight but should reflect situations that can occur in patients with incipient erosion (2.7 μm -4.8 μm). [25][26][27] As expected, in the present study, the profilometric analysis showed that the lowest tissue loss was observed in the fluoride-treated group (AmF/NaF/SnCl 2 solution containing 500 ppm F -, 800 ppm Sn 2+ , pH = 4.5) compared to the control group. The tin-containing solution was effective in inhibiting enamel surface loss in other in vitro 4,5,[28][29][30] and in situ 16,31 studies.…”
Section: Discussionsupporting
confidence: 86%
“…Each of the eight volunteers, worn their palatal devices containing 8 specimens, which were divided into four pairs as shown in Figure 1 and subjected to the challenges as described in Table 1. They were carried out extra orally in a single stage with the aid of a device made with Ethylene Vinyl Acetate (EVA) in accordance to Honorio et al (14), to delimit the area that would be eroded or/and abraded. The experiment was conducted in three phases in a crossover design.…”
Section: Intraoral/ Ex Vivo and Extraoral Phasesmentioning
confidence: 99%
“…Saliva may minimize the impact of theses challenges as well due to its properties of buffering capacity and ability do neutralize acidic products (3,(12)(13)(14). Even previous studies evidenced actual changes on enamel surface; the preconditioning with phosphoric acid would be enough to promote a reactive surface for bonding process, without the indication of roughening and allowing a more conservative approach (22).…”
Section: Impact Of Orange Juice On Bonding To Enamelmentioning
confidence: 99%
“…Several studies offered a better understanding of tooth wear and dental erosion and their potential risk factors. These published studies include in vitro and in situ studies [27][28][29][30][31][32][33], case-control studies [34][35][36][37], cross-sectional studies [38][39][40][41][42][43][44][45][46] and longitudinal studies [47][48][49]. The main aims of these studies were assessment of the prevalence of dental erosion or tooth wear and recognition of possible factors associated with its development and progression.…”
mentioning
confidence: 99%